2021
DOI: 10.1038/s41467-021-21721-3
|View full text |Cite
|
Sign up to set email alerts
|

Momentarily trapped exciton polaron in two-dimensional lead halide perovskites

Abstract: Two-dimensional (2D) lead halide perovskites with distinct excitonic feature have shown exciting potential for optoelectronic applications. Compared to their three-dimensional counterparts with large polaron character, how the interplay between long- and short- range exciton-phonon interaction due to polar and soft lattice define the excitons in 2D perovskites is yet to be revealed. Here, we seek to understand the nature of excitons in 2D CsPbBr3 perovskites by static and time-resolved spectroscopy which is fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 65 publications
(125 reference statements)
4
110
0
Order By: Relevance
“…A similar phenomenon has been observed in anthracene and few‐layer CsPbBr 3 . [ 8,31 ] However, E trap is much larger than E detrap in those two cases, [ 8,31 ] and consequently, STEs are metastable and can only be observed at high temperatures. For STEs reported in other 2D LHPs, E trap is generally much smaller than E detrap , leading to a minor detrapping efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar phenomenon has been observed in anthracene and few‐layer CsPbBr 3 . [ 8,31 ] However, E trap is much larger than E detrap in those two cases, [ 8,31 ] and consequently, STEs are metastable and can only be observed at high temperatures. For STEs reported in other 2D LHPs, E trap is generally much smaller than E detrap , leading to a minor detrapping efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanisms of such ultrafast processes are complicated and strongly depend on the lattice temperature, energy barriers (defined by the exciton–phonon coupling strength), sample quality, and so on. [ 8,19,21,22 ] For certain types of perovskites, the fluorescence shows nonexponential decay, indicating a dynamic dephasing process between free exciton states and self‐trapped states. [ 16,21,23 ] However, the physical mechanism of this phenomenon remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main peak arises from free exciton emission, while the lower energy tail is attributed to localized exciton emission due to strong exciton‐phonon coupling. [ 94 ] Interestingly, it was found that the higher spectral asymmetry with increasing the A‐cation size is correlated with the PL quenching (Table 1). This correlation emphasizes the importance of exciton phonon interaction in determining the PL properties.…”
Section: Stabilization Of Metastable Perovskite Lattices With Oversiz...mentioning
confidence: 99%
“…In recent years, lead halide perovskites have attracted great attention in the application of high-performance photovoltaic and optoelectronic because of their large optical absorption coefficient, low cost, simple preparation, etc. ( Gu et al., 2020 ; Guzelturk et al., 2021 ; Tao et al., 2021 , 2020 ; Wang et al., 2021a ; Wang et al., 2020 ) Photodetectors based on lead halide perovskites have been widely applied in diverse fields including optical communication, remote sensing, military surveillance, imaging technology, and industry automation control. However, it should be noted that the organic-inorganic lead halide perovskite possesses the poor stability which hinders the development of perovskite devices ( Li et al., 2019 ; Zhou and Zhao, 2019 ).…”
Section: Introductionmentioning
confidence: 99%